2011
DOI: 10.21236/ada558534
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Natural Pozzolan in Concrete as an Additive or Substitute for Cement

Abstract: Chemical, physical, and mechanical tests were conducted to assess the feasibility of using naturally occurring pozzolan as a cement mortar additive. One test series assessed the feasibility of substituting pozzolan for a portion of cement in concrete mortar mixtures. The chemical composition of five natural pozzolans was determined. Compressive testing was conducted on specimens with varying amounts and types of pozzolan. One pozzolan was found suitable for cement replacement in Type M mortars, and one was sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 7 publications
1
17
0
1
Order By: Relevance
“…As shown in Figure 5, a volcanic scoria from Syria reduced the heat of hydration [94]. Similar results were also reported by Alhozaimy et al [95] who concluded that the heat of hydration of VS-based cement pastes liberated in the first 72 h was, on average, 85% of the control mix.…”
Section: Heat Of Hydrationsupporting
confidence: 86%
“…As shown in Figure 5, a volcanic scoria from Syria reduced the heat of hydration [94]. Similar results were also reported by Alhozaimy et al [95] who concluded that the heat of hydration of VS-based cement pastes liberated in the first 72 h was, on average, 85% of the control mix.…”
Section: Heat Of Hydrationsupporting
confidence: 86%
“…2 se observa el comportamiento resistente con el tiempo de curado de las mezclas de CAC con caliza molida, lodo calcáreo, material volcánico (MVT y MVT/MVP) y la de la mezcla CAC65-FA-35, la cual presentó la mayor resistencia a la compresión a los 28 días de curado. La mezcla CAC 67_LP-33, que contenía una cantidad elevada de finos (675 kg/m 3 ), presentó un buen desempeño de la resistencia a la compresión, y esto es atribuido, según algunos investigadores [48], a que la piedra caliza en reemplazos pequeños acelera la hidratación del cemento debido a la creación de lugares de nucleación, lo cual influencia las reacciones de hidratación, además porque el uso de adiciones con grandes áreas superficiales puede conducir a una baja porosidad capilar y por lo tanto a aumentar la resistencia [49]. Con respecto a los CAC con material volcánico, todas las mezclas presentaron una menor resistencia con respecto a su mezcla de referencia (CAC 100_MVT-0) [50], y su evolución de resistencia no superó el 21% desde los 28 días de curado a los 90 días de curado para la mezcla con 30% de MVT (CAC 70_MVT-30), la cual presentó la mayor ganancia de resistencia en este periodo de tiempo; sin embargo, comparándola con la mezcla de referencia (CAC 100_MVT-0) la resistencia era 42,8% menor a los 28 días de curado.…”
Section: 21-resistencia a La Compresiónunclassified
“…From theoretical and experimental points of view, some authors (Al-Chaar et al 2011;Parhizkar et al 2010) have carried out works on the scoria behavior. In this study, an experimental protocol was set up to determine the composition of scoria concretes.…”
Section: Binary and Ternary Mixturesmentioning
confidence: 99%
“…A progressive reduction in the cement dosage was conducted with respect to the void ratio results. The quantities of fines used were calculated to account for the total value of the absolute volume of the mixture in cement substitution, which implies that fine scoria can be surely used as an additive or substitute for cement in concrete mixtures (Al-Chaar et al 2011). It is noted that Vr was reduced in order to increase the significance of the void ratio for specimens bc7 and bc8.…”
Section: Binary and Ternary Mixturesmentioning
confidence: 99%